Dampak Persaingan Dagang Terhadap Omzet Penjualan Bumbu Dapur Di Pasar Bukit Pamulang - Andryannisa, Mahesya Az-zahra; Kurniawati, Hartin; Wahyudi, Aradelia Pinkkan (JURNAL KAJIAN ISLAM MODERN, 2023)
This research aims to determine how business competition and the impact of competition on the income of traders, especially kitchen spice traders. This research was conducted in Bukit Pamulang Market. This reaserch used descriptive qualitative research. Researchers use primary data sources. Data collection techniques used in the form of observation, interviews and documentation. Furthermore, analyze the findings using theories related to the subject matter studied. The results of this research show that trade competition has a major impact on the income of spice traders. In addition, revenue also affects the number of competitors, the more new competitors have an impact on other competitors. At the Mba Emi shop, the decrease in turnover over the last 5 years was 48%. At Uni Diyah stalls as much as 47%. And at Opung stalls it is as much as 48%. Keyword : Impact of Trade Competition, Sales Turnover, Herbs